Peningkatan Pengetahuan Masyarakat Tentang Pemanfaatan Tanaman Herbal Dalam Rangka Pencegahan Penyakit Diabetes Mellitus - Wulandari, RR Sri; Prawistya Sari, Agnes; Triana, Lanny; Wardhana Amrullah, Adhi (CV RIFAINSTITUT, 2023)
Diabetes is a chronic disease with an increasing prevalence and a threat to global health. Many people are still not aware of the importance of maintaining health in order to prevent degenerative diseases in old age. Moreover, nowadays there are so many ready-to-eat foods that have the potential to cause many diseases, one of which is diabetes mellitus. The community service team provides counseling to increase understanding and insight into the importance of using herbal medicine in the context of preventing diabetes mellitus. The results of community service counseling attended by 30 participants can be concluded that with this counseling the community is very enthusiastic and welcomes this activity as seen from the questions raised. This activity provides insight for the people of Gumpang Village, especially the types of herbal plants that can lower blood glucose levels.